KOORDINASI PENANGANAN PENYALAHGUNAAN NARKOTIKA MELALUI TIM ASESMEN TERPADU DI KOTA CIMAHI - Rio Aryandi Erlangga; Darto Darto; Hilman Abdul Halim (Universitas Padjadjaran, 2023)
Based on the problems that occurred in the coordination of the handling of narcotics abuse through the Integrated Assessment Team in Cimahi City, several basic obstacles were found, such as the lack of budget and the ineffectiveness of the implementing agencies, the existence of official mutations in the implementing agencies appointed as the Integrated Assessment Team. The researcher uses the theory of success factors for coordination from the State Service Commission which has 3 dimensions, namely the mandate dimension, the system dimension, and the behavioral dimension. The purpose of this study is to describe the coordination of the handling of narcotics abuse through the Integrated Assessment Team in Cimahi City which has not been effective. This study uses a qualitative method in which the author conducts interviews with several informants, then will look for data through related documents to strengthen the data that has been obtained from interviews. The results obtained are that the three dimensions that have been described have not been implemented properly. Therefore, researchers provide suggestions related to the coordination of handling narcotics abuse through the Integrated Assessment Team, it is necessary to make efforts to the budget for the implementation of the assessment by the Integrated Assessment Team, better coordination is carried out directly to the members of the Integrated Assessment Team Berdasarkan permasalahan yang terjadi dalam koordinasi penanganan penyalahgunaan narkotika melalui Tim Asesmen Terpadu di Kota Cimahi ditemukan beberapa kendala yang mendasar seperti kurang nya anggaran serta belum efektifnya instnasi pelaksana, adanya mutasi dinas pada instnasi pelaksana yang ditunjuk menjadi Tim Asesmen Terpadu. Peneliti menggunakan teori factor-faktor keberhasilan koordinasi dari State Service Commission yang memiliki 3 dimensi, yaitu dimensi mandate, dimensi system, dan dimensi perilaku. Tujuan dari penelitian ini adalah untuk mendeskripsikan koordinasi penanganan penyalahgunaan narkotika melalui Tim Asesmen Terpadu di Kota Cimahi yang belum efektif. Penelitian ini menggunakan metode kualitatif yang mana penulis melakukan wawancara dengan beberapa informan, lalu akan mencari data melalui dokumen-dokumen terkait untuk meguatkan data yang telah didapatkan dari wawancara. Hasil yang didapatkan adalah bahwa dari ketiga dimensi yang telah diuraikan masih belum terlaksana dengan baik. Maka dari itu, peneliti memberikan saran terkait koordinasi penanganan penyalahgunaan narkotika melalui Tim Asesmen Terpadu perlu melakukan upaya terhadap anggaran pelaksanaan asesmen oleh Tim Asesmen Terpadu, koordinasi yang dilakukan lebih baik langsung kepada anggota Tim Asesmen Terpadu